A study on cognitive metaphors denoting the concept of “life” in lyric songs in english versus vietnamese - Hoàng Nguyễn Tôn Ngân (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
In light of Cognitive Linguistic, Metaphor is defined as understanding one conceptual domain in term of another conceptual domain. In addition, this is believed to be an important tool in human cognition and thought as well as a vital role in the conceptualization of abstract aspects. The concept of “life” is also considered as one of the abstract entity having close relations with cognition. Therefore, this paper attempts to conduct a contrastive analysis research of conceptual metaphor of “life” in English and Vietnamese. To achieve the purposes, this paper chooses the descriptive, quantitative and qualitative approaches throughout the study. There are approximately 350 metaphorical expressions of “life” collected from American and Vietnamese songs in books and on the Internet. The findings presented ten source domains which occur in conceptual metaphors of “life” in American, Vietnamese, or both. We found that American and Vietnamese share a lot of conceptual metaphors of “life”. However, only three kind of conceptual metaphors denoting the concept of “life” occurs in American while there remains some conceptual metaphors of “life” that occurs in Vietnamese but not in American. Basing on the findings of the thesis, some implications for teaching, learning and translating of conceptual metaphors will be suggested. Furthermore, this thesis is useful for Vietnamese learners of English to be successful in cross- cultural communication.